Factors Affecting the Low Delivery by Health Workers in Ciakar Village, Tangerang Regency - Rosmiati, Rosmiati; Anggraini, Aulia Hervi; Sagita, Widi (Akademi Keperawatan RSPAD Gatot Soebroto, 2022)
The high maternal mortality rate in Indonesia is caused by 32% of births being assisted by traditional birth attendants. Delivery assisted by medical personnel is closely related to efforts to reduce infant mortality and maternal mortality. Even though the movement is slow, it definitely shows improvement compared to those who are assisted by non-medical personnel (midwife). The purpose of this study was to determine the relationship between attitude and the selection of birth attendants for pregnant women in Ciakar village, Tangerang district. The research method used is the analytical method. The population and sample of the study were 68 pregnant women. Data analysis with univariate and bivariate analysis. The results of univariate analysis, pregnant women based on the selection of birth attendants (52.9%) showed that the majority of pregnant women chose non-health workers, pregnant women based on their attitudes towards the selection of birth attendants (73.5%) showed that the majority of pregnant women have a disapproving attitude towards the selection of birth attendants with health workers. The results of the bivariate analysis showed that there was a relationship between attitudes and the selection of birth attendants for pregnant women (P=0.001).